A mollicute (mycoplasma) DNA repair enzyme: purification and characterization of uracil-DNA glycosylase. - Williams, M V (1990)
The DNA repair enzyme uracil-DNA glycosylase from Mycoplasma lactucae (831-C4) was purified 1,657-fold by using affinity chromatography and chromatofocusing techniques. The only substrate for the enzyme was DNA that contained uracil residues, and the Km of the enzyme was 1.05 +/- 0.12 microM for dUMP containing DNA. The product of the reaction was uracil, and it acted as a noncompetitive inhibitor of the uracil-DNA glycosylase with a Ki of 5.2 mM. The activity of the enzyme was insensitive to Mg2+, Mn2+, Zn2+, Ca2+, and Co2+ over the concentration range tested, and the activity was not inhibited by EDTA. The enzyme activity exhibited a biphasic response to monovalent cations and to polyamines. The enzyme had a pI of 6.4 and existed as a nonspherical monomeric protein with a molecular weight of 28,500 +/- 1,200. The uracil-DNA glycosylase from M. lactucae was inhibited by the uracil-DNA glycosylase inhibitor from bacteriophage PBS-2, but the amount of inhibitor required for 50% inhibition of the mycoplasmal enzyme was 2.2 and 8 times greater than that required to cause 50% inhibition of the uracil-DNA glycosylases from Escherichia coli and Bacillus subtilis, respectively. Previous studies have reported that some mollicutes lack uracil-DNA glycosylase activity, and the results of this study demonstrate that the uracil-DNA glycosylase from M. lactucae has a higher Km for uracil-containing DNA than those of the glycosylases of other procaryotic organisms. Thus, the low G + C content of the DNA from some mollicutes and the A.T-biased mutation pressure observed in these organisms may be related to their decreased capacity to remove uracil residues from DNA.